(untitled) (Interdisciplinary Studies Journal, 2026)
Based on the intersectionality framework, this study aims to understand the phenomenon of property violence against women by considering gender, race, and class dimensions from both Brazilian and international perspectives. To this end, a review of the national and international scientific literature was conducted using the CAPES Journal Portal database, covering the last five years, from 2019 to 2024. This literature review seeks to analyze scientific publications in peer-reviewed journals, taking into account criteria of gender, race, and class intersectionality in studies addressing property violence against women. After applying the inclusion and exclusion criteria, four national studies and eleven international studies were retrieved. The results indicate that studies on the topic discuss the intersectionality of gender and class, particularly with regard to women in situations of social vulnerability, while studies that delve deeper into the racial dimension remain scarce. The importance of considering other intersectionality criteria in future studies is emphasized, such as the forms in which property violence affects older women and women with disabilities. Understanding this complex phenomenon is necessary for the proper implementation of public policies aimed at preventing and combating gender-based violence and other rights violations.